Simulation of Taxation of Enterprises - Ievsieieva, Olga; ., . (International Journal of Engineering and Technology, 2018)
In the article, a taxation methodology is proposed for enterprises of the agricultural sector of the economy which allows forecasting tax revenues. The model is based on the correlation and regression analysis. The author suggests using the paired comparison and prioritization methods for the scientific rationale of the choice of the model. The effectiveness of the company's fiscal policy is determined based on the value of the coefficient, which is calculated as the ratio of the actual amount of collected taxes to their amount obtained by calculation using the regression equation. The methodology can be used by the managers of the agricultural sector of the economy to compare the performance of the enterprises and the rationale for incentives. The utilization of the results of the analysis is reasonable for justification of investment projects with the objective of developing the agricultural sector of the regional economy.Â Â Â